The impact of water management and nitrification inhibitors on methane emissions from paddy soil - Wenli Cui; Xiaoxiao Li; Wenjun Jin; Ning Zhou; Zhaorong Dong (PLoS ONE, 2026)
Methane (CH₄) is a potent greenhouse gas, and rice paddies are a major source of agricultural CH₄ emissions. Water management and nitrification inhibitors can significantly affect CH 4 emissions, but their coupled effects on rhizospheric CH₄ emissions remain unclear. This study employed a rhizobox experiment to investigate the effects of three water management practices—continuous flooding irrigation (C), wetting irrigation (W), and alternate wetting and drying irrigation (A)—and the nitrification inhibitor DMPP (3,4-dimethylpyrazole phosphate) on CH₄ emissions from rice paddies. The results revealed that the rhizosphere was the primary zone for CH₄ emissions, with fluxes up to eight times greater than those from the bulk soil. In all the treatments, peak CH₄ emissions consistently occurred during the rice maturity stage. This peak is attributed to increased carbon availability from root senescence, coupled with soil redox conditions primarily dictated by the respective water management regime. Water management emerged as the primary driver of emission reduction. Compared with C, A significantly reduced cumulative CH₄ emissions by approximately 83.0% in the bulk soil and by 96.9% in the rhizosphere. The application of DMPP further enhanced this mitigation effect, particularly under W and C conditions, leading to an additional 23.06% to 35.94% reduction in bulk soil CH₄ emissions. The observed mechanisms of DMPP addition likely extend beyond its traditional role as a nitrification inhibitor. In conclusion, alternating wetting and drying irrigation with DMPP addition most effectively suppressed CH₄ emissions by synergistically regulating water–carbon–nitrogen coupling processes. This study highlights the central role of rhizospheric processes in reducing emissions, providing a deeper theoretical foundation for developing targeted low-carbon management strategies for rice paddy cultivation.